Metabolic reprogramming: A novel therapeutic target in diabetic kidney disease - Wang, Mengdi; Pang, Yanyu; Guo, Yifan; Tian, Lei; Liu, Yufei; Shen, Cun; Liu, Mengchao; Meng, Yuan; Cai, Zhen; Wang, Yuefen; Zhao, Wenjing (Frontiers in Pharmacology, 2022)
Diabetic kidney disease (DKD) is one of the most common microvascular complications of diabetes mellitus, However, the pathological mechanisms contributing to DKD are multifactorial and poorly understood. Diabetes is characterized by metabolic disorders that can bring about a series of changes in energy metabolism. As the most energy-consumption organs only secondary to the heart, the kidneys must maintain energy homeostasis. Aberrations in energy metabolism can lead to cellular dysfunction or even death. Metabolic reprogramming, a shift from mitochondrial oxidative phosphorylation to glycolysis and its side branches, is thought to play a critical role in the development and progression of DKD. This review focuses on the current knowledge about metabolic reprogramming and the role it plays in DKD development. The underlying etiologies, pathological damages in the involved cells and potential molecular regulators of metabolic alterations are also discussed. Understanding the role of metabolic reprogramming in DKD may provide novel therapeutic approaches to delay its progression to end-stage renal disease (ESRD).